A review of cutaneous manifestations of HTLV-associated adult T-cell leukemia/lymphoma - LeWitt, Tessa M.; Gru, Alejandro A. (Frontiers in Medicine, 2025)
Adult T-cell leukemia/lymphoma (ATLL) is a rare aggressive mature T-cell neoplasm caused by the human T-cell leukemia virus type 1 (HTLV-1). The disease predominantly affects patients from endemic regions of Japan, the Caribbean, Sub-Saharan Africa, and South America. Cutaneous involvement of ATLL is common and may appear before or in the absence of systemic involvement. However, the lesions are non-specific and often mimic more common inflammatory and neoplastic skin diseases, making diagnosis challenging. Moreover, morphology is variable among patients, ranging from macules and papules to tumors and erythroderma. Recent data suggests that the presence of cutaneous lesions and lesion morphology are important for prognostication and for guiding treatment. Here, we provide an overview of the spectrum of cutaneous findings in ATLL, highlighting their diagnostic, prognostic, and therapeutic implications. We emphasize the importance of early recognition and workup of suspicious skin lesions, particularly in endemic regions or high-risk populations. Finally, we describe fundamental concepts and controversies, and highlight current knowledge gaps.